Assessing Willingness to Pay for Parking Fees Among Residents: Evidence from Malang City - Anggoro, Damas Dwi; Shofwah, Aleyda Farihatus (UI Scholars Hub, 2025)
This study aims to investigate the willingness to pay (WTP) for user charges imposed by the local government using an extended Theory of Planned Behavior (TPB). Viewing the local government as a service provider, the construct of perceived value is incorporated to determine behavioral intention toward user charges, marking a novel contribution of this study to the literature. Specifically, this study analyzes (1) the effect of each TPB construct—attitude toward the behavior, subjective norms, and perceived behavioral control (PBC)—on WTP, (2) the effect of perceived value on WTP, and (3) the indirect effect of perceived value on WTP mediated by TPB constructs. This study applied a cross-sectional survey with a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings indicate that attitude does not significantly influence WTP, while subjective norms, PBC, and perceived value are significant predictors. The indirect relationship between perceived value and WTP was observed only through subjective norms and PBC.